Prototype of solar collector with recirculation of nanofluids, for a convective dryer - Vania Sbeyde Farias-Cervantes; Denis Del Sagrario Garcia-Marquez; Isaac Andrade-Gonzalez; Arturo-Moises Chavez-Rodriguez; Mayra I Montero-Cortes (International Journal of Renewable Energy Development, 2022)
The research is based on the design, construction, and evaluation of a flat-layer solar collector using nanofluids. It has the following dimensions 1 m2 by 20 cm in height, a 9 mm thick tempered glass, a heat exchanger, where nanofluids circulate, and an angle of inclination of 45 °. Nanofluids were designed based on canola oil and nanopowders of size> 50 nm of Al2O3, CuO, and a 1: 1 mixture of both; Its thermal profile was determined using the Differential Scanning Calorimetry (DSC) technique. The temperatures of the solar collector were recorded in an Agricos® unit. As a result, the maximum peaks of the air leaving the collector were as follows. 39.1 ° C, 44 ° C, 54 ° C and 47.1 ° C, for canola oil, nanofluids Al2O3, CuO, and the 1: 1 mixture respectively. it is observed that there is an increase in the outlet air temperature using nanofluids.